2011
DOI: 10.1097/mph.0b013e3181f69205
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Tonsillar Enlargement With Strong 18F-FDG Uptake After Chemotherapy for Tonsillar Diffuse Large B-cell Lymphoma

Abstract: We describe a 14-year-old boy who exhibited left palatine tonsillar enlargement after 6 cycles of aggressive chemotherapy for diffuse large B-cell lymphoma of the right palatine tonsil. The cervical computed tomography scan at 4 months after completion of chemotherapy revealed enlargement of the left palatine tonsil in addition to the thymus without any clinical symptoms. The F-fluorodeoxyglucose positron emission tomography indicated focal areas of strong F-fluorodeoxyglucose uptake in the left palatine tonsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 7 publications
(10 reference statements)
3
14
0
Order By: Relevance
“…To our knowledge, it is the second case of histologyproven RFH affecting the palatine tonsil with strong 18 F-FDG uptake [8] and we suggested that chemotherapy is probably related with this finding.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…To our knowledge, it is the second case of histologyproven RFH affecting the palatine tonsil with strong 18 F-FDG uptake [8] and we suggested that chemotherapy is probably related with this finding.…”
Section: Introductionmentioning
confidence: 58%
“…To the best of our knowledge, there is only one case of palatine tonsil RFH showing 18 F-FDG uptake in a 14-year-old boy after 6 cycles of aggressive chemotherapy for diffuse large B cell lymphoma [8]. It is interesting the fact that several RFH cases, usually affecting the tonsils, lymph nodes and thymus gland, in patients with hematological malignancies after chemotherapy have been reported [8,11,12,22]. In these cases, it is often difficult to distinguish RFH from residual or recurrent disease, even if various imaging modalities are used.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[4] In lymphoma patients, unfortunately, false-positive results are possible, because an infection, inflammation, hypermetabolic brown fat surrounding lymph nodes or reactive process producing strong 18F-FDG uptake might be present. [2,[5][6][7][8] In these cases, and not uncommonly after chemotherapy, reactive enlargement of the lymph nodes, tonsils, and thymus gland can be detected. [8][9][10]…”
mentioning
confidence: 99%